Severe Ileocolonic Crohn's Disease Flare Associated with Fecal Microbiota Transplantation Requiring Diverting Ileostomy. Issue 1 (2018) - Tran, Vivy; Phan, Jennifer; Nulsen, Benjamin; Huang, Lizhou; Kaneshiro, Marc; Weiss, Guy; Ho, Wendy; Sack, Jonathan; Ha, Christina; Uslan, Daniel; Sauk, Jenny S.
ABSTRACT : N/A: Patients with inflammatory bowel disease (IBD) are at increased risk of developing Clostridium difficile infection (CDI). Fecal microbiota transplantation (FMT) is an effective therapy with a high success rate in preventing recurrent CDI. However, patients with IBD have decreased response to FMT for recurrent CDI, with several reports also suggesting potential IBD flare post‐FMT. We present a case of mild ileocolonic Crohn's disease in a patient treated with FMT for recurrent CDI who subsequently developed severe steroid‐refractory flare requiring surgical intervention 1 week post‐FMT. Greater understanding of risk factors associated with post‐FMT IBD flare is indicated.